The Path to Clarity: Development of Property Rights in China - Huang, Frank Xianfeng (Columbia Journal of Asian Law, 2004)
The clear demarcation of property rights is no longer purely an issue of academic interest in China. To a large extent, it has already become a vital policy and lemislative concern. In President Jiang Zemin’s 1997 report to the 15 CCP National Congress, “readjusting and perfecting” China’s ownership structure was made a fundamental strategy to build an efficient socialist market economy and to maintain sustained economic growth.’ Shortly after this policy breakthrough, the drafting of a comprehensive Law on Real Property Rights (wuquanfa) was put on the working agenda of the Legislative Affairs Committee of the National People’s Congress (LAC) in 1998. Two teams of civil law scholars were entrusted with working on drafting the law. One team was led by Professor Huixing Liang of Chinese Academy of Social Science and the other by Professor Liming Wang of Chinese People’s University. The two teams each submitted a proposed draft to the Legislative Affairs Committee. In 2001, the two proposed drafts were combined into one and the resulting LAC draft (zhengqiu yijian gao) is currently being circulated for comments. Of the many legislative objectives the new law is designed to achieve, clarifying property relationships among various economic actors is the overarching goal of the proposed law.